Deciphering the dynamics of financing choices in Indonesian micro-industries: An empirical analysis of internal and external sources - Sofia, Myrna (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This study analyzes micro-industry characteristics influencing their choice between internal (own capital) and external financing sources (venture capital, banks, and others). A sample size of 83,616, derived from the BPS Survey, was employed for this purpose. Logistic regression analysis was utilized to address the research questions. The findings suggest that own capital financing predominantly supports micro-industries that are small in scale, possess a low business entity status, have mature owner age, have owners with higher educational backgrounds, and exhibit minimal innovation. Conversely, venture capital financing is more inclined towards larger micro-industries with increasing maturity and more innovations. Bank financing is typically allocated to younger micro-industries with higher business entity status, younger owners, lower income, and those incorporating internet usage. Other forms of capital financing are more likely to be selected by micro-industries with owners who have a lower educational background. The characteristics of micro-industries significantly enhance the probability of opting for bank financing. The educational background of the owner is a critical factor in choosing one's own capital and venture capital financing. In contrast, the size of the micro-industry plays a pivotal role in selecting bank and other capital financing.